Pengaruh Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan (Study Pada PT. Bank BNI Kantor Kas Pakis Kota Malang) - Ike Ratnasari; Ayu Dhita Kartika (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
The role of human resources in the company is very important because as the main driver of all company activities in achieving goalscompany in order to maintain the success and survival of the company then a leader always maintains and improves the resources he hasThis includes paying attention to the work environment to improve performance his employees.Based on the objectives, this research was conducted to determine whether or not whether or not the influence related to the work environment with the performance of employees at PT Bank BNI Cash Office Pakis Malang. So in accordance with this purpose, This research is a type of causal quantitative research, namely: causal relationship, and includes explanatory researchwhich is descriptive in nature where this study aims to find an explanation why an event occurs.The conclusion from the results of this study is that it has been proven that there is an effect of significant on the variables of the Physical Work Environment (X1) and Non. Work Environment Physical (X2) Against Employee Performance (Y) either partially or partially simultaneous.Keywords: Physical Work Environment, Non-Physical Work Environment, Performance Employee, Explanatory Research